A coefficient inequality for the class of analytic functions in the unit disc - Yaşar Polatoğlu; Metın Bolcal (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to give a coefficient inequality for the class of analytic functions in the unit disc D={z||z| <1}.